2016
DOI: 10.1177/0165025415626515
|View full text |Cite
|
Sign up to set email alerts
|

Mediating pathways in the socio-economic gradient of child development

Abstract: Research has previously shown a gap of near 0.5 of a standard deviation (SD) in cognition and language development between the top and bottom household wealth quartile in children aged 6–42 months in a large representative sample of low- and middle-income families in Bogota, using the Bayley Scales of Infant and Toddler Development. The gaps in fine motor and socio-emotional development were about half that size. Developmental deficits increased with age. The current study explored the associations amongst chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 22 publications
7
45
0
4
Order By: Relevance
“…This is consistent with our hypothesis that because the state of malnutrition and sanitation is worse in the Amazon region, there is higher prevalence of developmental delay [21,22,30]. A study in Colombia found that the two most predictive indicators for cognitive and language development in children are maternal education and quality of home environment [19]. A study in Peru that compared ASQ scores to socioeconomic indicators on early child development also found that early child development (ASQ scores) was significantly impacted by household wealth and maternal education (p<0.01 and p<0.05) [10].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with our hypothesis that because the state of malnutrition and sanitation is worse in the Amazon region, there is higher prevalence of developmental delay [21,22,30]. A study in Colombia found that the two most predictive indicators for cognitive and language development in children are maternal education and quality of home environment [19]. A study in Peru that compared ASQ scores to socioeconomic indicators on early child development also found that early child development (ASQ scores) was significantly impacted by household wealth and maternal education (p<0.01 and p<0.05) [10].…”
Section: Discussionsupporting
confidence: 89%
“…The ASQ has been validated as an effective assessment tool for developmental delay in a wide-range of contexts and is significantly less time consuming and more inexpensive to administer [17]. The ASQ is a feasible evaluation tool for large scale deployments for prevalence studies and program [10,14,18,19]. The ASQ has been validated for test-retest in Spanish, including in the context of the Amazon of Peru, and found reliability scores of .80-.85 (differing by section)[18].…”
Section: Methodsmentioning
confidence: 99%
“…ed.). Una mayor asociación entre educación de la madre y desarrollo infantil -con valores de entre 0,12 y 0,17 para el SAF y entre 0,05 a 0,11 para el SCD-que entre educación del padre y desarrollo infantil -con valores de entre 0,07 y 0,12 para el SAF y entre 0,05 y 0,08 para el SCD-también ha sido documentada con anterioridad (Schady, 2011;Hamadani et al, 2014;Rubio-Codina, Attanasio y Grantham McGregor, 2016b).…”
Section: Correlación De Los Puntajes Del Asq-3 Con Variables Socioecounclassified
“…En particular, las correlaciones entre materiales de juego según uso y, especialmente, entre actividades de juego y desarrollo infantil, son de mayor magnitud que las observadas entre desarrollo infantil y educación de la madre o nivel de riqueza del hogar. Esto guarda coherencia con el importante rol mediador que cumple el nivel de estimulación en el entorno para el desarrollo infantil (Walker et al, 2011;Hamadani et al, 2014;Rubio-Codina, Attanasio y Grantham McGregor, 2016b).…”
Section: Correlación De Los Puntajes Del Asq-3 Con Variables Socioecounclassified
See 1 more Smart Citation